Mode Selection Model Based on Travel Time and Price of Goods with Regression Analysis Model - Yessy Yusnita; Lita Lovia (Department of Mathematics, Universitas Negeri Padang (UNP), 2024)
Padang City Market is one of the shopping centres in Padang City, which is located in the West Padang District. The shopping centre presents a place for people to buy kitchen supplies or basic daily needs. This makes the area quite attractive for community travel. This research was conducted on 400 respondents who visited Padang City Market. In this study, the choice of mode is represented by the Y variable and is categorized into private vehicles, public transportation, rental vehicles, walking, and others. The travel time variable represents X1. The variable price of goods represents X2. This study aims to assess the level of correlation between the choice of mode (Y) on the variable travel time (X1) and the variable price of goods (X2). Furthermore, the mode selection (Y) was modeled based on the variables X1 and X2 using linear regression analysis with SPSS tools. The results of the analysis show a strong relationship between the Y variable and the X1 and X2 variables. The best linear regression model produced is Y = 0,010 + 0,76X1 + 0,029X2 with a value of R = 0,437. This means that the closer the travel time is and the lower the price of goods, the more the intensity of motorcycle mode selection to Pasar Raya Padang increases.